Institutions, distributed cognition and agency: rule-following as performative action - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
Recently, Aoki proposed the concept of substantive institutions which relates outcomes of strategic interaction with public representations of equilibrium states of games. I argue that the Aoki model can be grounded in theories of distributed cognition and performativity, which I put into the context of Searle's philosophical account of institutions. Substantive institutions build on regularized causal interactions between internal neuronal mechanisms and external facts, which are shared in a population of agents. Following Searle's proposal to conceive rule following as a neuronally anchored behavioral disposition, I show that his corresponding notion of collective intentionality can be grounded in recent neuroscience theories about imitation as the primordial process in human learning. I relate this with Searle's concept of status function and the neuronal theory of metaphors, resulting in a precise definition of rule-following as performative action. I present two empirical examples, the institution of money and status hierarchies in markets.
Keywords: B52; D02; D87; 330; Aoki's concept of substantive institutions; Searle; collective intentionality; emotions; imitation; performativity; sign systems